Influence of pilates and quick massage on depression, anxiety and fatigue in banking sector workers: a randomized controlled trial - Barbosa, Danillo; Oliveira, Renata Michele Angelo de; Kerppers, Ivo I.; Xavier, Gabriela; Ferreira, Mônica Beatriz (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The health of the worker is inserted within the public health, and comprises a link between production, work and health. Objectives: This study aims to analyze the influence of quick massage and pilates on the level of depression, anxiety and fatigue in employees of a bank. Method: This is a clinical, controlled, randomized, blind study. The study had 70 subjects, but only 50 were included. They were divided into 3 groups: quick massage group (n= 20), pilates group (n= 20) and control group (n= 10). They were evaluated in 3, 6 and 9 months and the protocol was applied 3 times per week. Results: the results were expressed as mean and standard deviation, followed by the univariate analysis of variance (ANOVA), obtaining a value of p<0.0198. However, it was observed, when presenting the detailed data of each group (mean and standard deviation), that the quick massage group presented a small advantage with 4.03 ± 0.82 (6 months) and 3.43 ± 1.15 (12 months), whereas the pilates group were 6.21 ± 1.98016 (3 months), 4.26 ± 0.57873 (6 months) and 4.14 ± 0.63 (9 months). Conclusion: it is concluded that the quick massage techniques and the Pilates protocol have shown great potential in the reduction of anxiety, depression and fatigue.